Enhancing Diabetes Self-care Among Rural African Americans With Diabetes: Results of a Two-year Culturally Tailored Intervention. (March 2014) - Williams, Ishan C.; Utz, Sharon W.; Hinton, Ivora; Yan, Guofen; Jones, Randy; Reid, Kathryn
Purpose: The purpose of this study is to test the feasibility of conducting a community-based randomized controlled trial evaluating a culturally tailored community-based group diabetes self-management education (DSME) program among rural African Americans. Methods: Thirty-two African American rural adults with type 2 diabetes were recruited and 25 adults were retained and participated in an interventional study designed to test the effectiveness of the "Taking Care of Sugar" DSME program for the 2-year follow-up. Participants were selected from rural central Virginia. Primary outcomes variables included average blood sugar levels, cardiovascular risk factors, and general physical and mental health. These outcomes were assessed at baseline, 3 months, 6 months, and 12 months post baseline. Results: From baseline to 3-month follow-up assessment, participants exhibited significant improvement on several physiological and behavioral measures. Given the small sample size, hypothesis testing was limited. Results show change from baseline over time, illustrating that the primary outcome of A1C decreased, although not significant. Additionally, participants reported more knowledge about diabetes self-management and personal care skills (ie, exercise and foot care) that persisted over time. The feasibility of the culturally tailored DSME was established, and participation with the program was high. Conclusions: A community-based group DSME program using storytelling is feasible. This research will help to inform clinicians and health policymakers as to the types of interventions that are feasible in a larger rural population. If such a program is carried out, we can improve knowledge, reduce complications, and improve quality of life among rural African Americans.